The Impact of Cocoa Cultivation on Soil Characterstics in Southwestern Nigeria - Ekanad, Olusegun (Obafemi Awolowo University, 2014)
This study investigates the impact of cocoa cultivation on soil properties in a part of the Nigerian Cocoa Belt with a view to providing a framework for land use planning and management. For comparative purposes, the conditions under forest and fallow were also investigated.